Women Domestic Workers Reveal Secrets of the Trade. (3rd July 2021) - Ma, Xiang; Chen, Melinda
Abstract : Rather than simply lamenting migrant workers' everyday struggles and harsh working conditions, Ma Xiang's essay seeks to provide a structural analysis of the socioeconomic injustice facing tens of millions of domestic helpers. Strengthening an insider's plain account with narrative strategies of reportage literature and investigative journalism, this short piece demonstrates migrant workers' unrecognized capacity to make a critical examination of the systematic exploitations and inequalities in a capital-dominant world.